2018
DOI: 10.1016/j.surfcoat.2018.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Improving the corrosion properties of amorphous Ni-P thin films using different additives

Abstract: 6Highlights 7  Effects of various additives on the corrosion resistance of Ni-P films is studied. 8 Thinner, more uniform, and smoother Ni-P thin films are formed with additives. 9 Excellent improvement of the corrosion resistance is observed. 11 Abstract 12Ni-P amorphous coatings are considered as important engineering alloys. In this paper, the effects 13 of various additives on the properties of Ni-P thin films were investigated, including saccharine, 14 glycine, pyridinium propyl sulfonate, coumarin, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…A thinner coating with more surface coverage ( Ѳ = 0.99) was obtained in the presence of additive (250 ppm) in the bath, which implies a uniform and smoother coating. Even so, the decrease in thickness may be influenced by the additives in the bath through a water side reaction [46]. The current efficiency is found to be higher (51%) in the case of alloy deposits with lower tungsten (39.68 wt%) and for higher tungsten percentage it was of lower current efficiency (45%) (Table 4).…”
Section: Resultsmentioning
confidence: 98%
“…A thinner coating with more surface coverage ( Ѳ = 0.99) was obtained in the presence of additive (250 ppm) in the bath, which implies a uniform and smoother coating. Even so, the decrease in thickness may be influenced by the additives in the bath through a water side reaction [46]. The current efficiency is found to be higher (51%) in the case of alloy deposits with lower tungsten (39.68 wt%) and for higher tungsten percentage it was of lower current efficiency (45%) (Table 4).…”
Section: Resultsmentioning
confidence: 98%
“…According to Figure 1 e, the analysis of the most influential parameters revealed that higher pH, lower stirring rate and higher reducing agent concentration led to coatings characterized by lower corrosion rates. Complexing agents and stabilizers present in ENP baths have been described as corrosion performance modifiers [ 41 , 42 ]. However, the concentration of the complexing agents had little influence on the corrosion performance of the studied NiP coatings according to the S/N ratio values in Figure 1 e.…”
Section: Resultsmentioning
confidence: 99%
“…However, coatings with higher Mn contents were found to have a lower corrosion resistance [101]. The incorporation of more Mn occurred in the presence of a higher concentration of glycine that has a negative effect on the corrosion resistance of thin films [155].…”
Section: Ni-crmentioning
confidence: 96%
“…The authors have recently published a paper about improving the corrosion behavior of Ni-P films using organic additives [155]. To summarize, the chemical composition, surface morphology, and crystalline structure of some of the Ni alloy deposits are presented in Table 1.…”
Section: Ni-crmentioning
confidence: 99%